Effects of High-Pressure Processing, UV-C Irradiation and Thermoultrasonication on Donor Human Milk Safety and Quality - Kontopodi, Eva; Stahl, Bernd; van Goudoever, Johannes B.; Boeren, Sjef; Timmermans, Rian A. H.; den Besten, Heidy M. W.; Van Elburg, Ruurd M.; Hettinga, Kasper (Frontiers in Pediatrics, 2022)
Holder pasteurization (HoP) is the current recommended treatment for donor human milk. Although this method inactivates microbial contaminants, it also negatively affects various milk components. High-pressure processing (HPP, 400, 500 and 600 MPa), ultraviolet-C irradiation (UV-C, 2430, 3645 and 4863 J/L) and thermoultrasonication (TUS, 1080 kJ/L and 1620 kJ/L) were investigated as alternatives to thermal pasteurization (HoP). We assessed the effects of these methods on microbiological safety, and on concentration and functionality of immunoglobulin A, lactoferrin, lysozyme and bile salt-stimulated lipase, with LC-MS/MS-based proteomics and activity assays. HoP, HPP, TUS and UV-C at 4863 J/L, achieved a >5-log10 microbial reduction. Native protein levels and functionality showed the highest reduction following HoP, while no significant reduction was found after less intense HPP and all UV-C treatments. Immunoglobulin A, lactoferrin and lysozyme contents were also preserved after low intensity TUS, but bile salt-stimulated lipase activity was significantly reduced. This study demonstrated that HPP and UV-C may be considered as suitable alternatives to HoP, since they were able to ensure sufficient microbial inactivation while at the same time better preserving the bioactive components of donor human milk. In summary, our results provide valuable insights regarding the evaluation and selection of suitable processing methods for donor human milk treatment, which may replace HoP in the future.